Crystal phase and morphology engineering of ω-Li3V2O5 nanospheres for high-rate lithium-ion capacitors. Issue 2 (9th December 2022) - Ren, Zhenghong; Yu, Shunzhi; Yao, Tengyu; Xu, Tiezhu; He, Juhong; Shen, Laifa
Abstract : Lithium ion capacitors provide both high energy and high power density. Li3 V2 O5 //AC, which is based on Li3 V2 O5 nanospheres with fast kinetics reveals the potential for the application in high rate and long lifespan energy storage devices. Abstract : Lithium ion capacitors (LICs) as promising energy storage devices are receiving lots of attention recently. However, anodes with high rate performance are urgently needed to balance the thermodynamics and kinetics of the cathode and the anode. Here, we report a morphology structure strategy to enhance the rate properties of disordered rock-salt Li3 V2 O5 (DRS-LVO) based on crystal phase engineering. Li3 V2 O5 nanospheres (LVO-NSs) deliver a low average insertion voltage (∼0.6 V vs. Li + /Li), excellent rate capability, and outstanding cycling stability (more than 85% capacity is retained after 6000 cycles) in half-cell devices. The electrode kinetics study shows that the novel nanosphere morphology endows LVO-NSs with more capacitive capacity contribution and a rapid ion transport path. The first-principles calculations indicate the energy storage and transport mechanism of LVO-NSs, in which Li + migrates into the lattice along the (110) plane with the lowest energy. A LIC with outstanding electrochemical performance is assembled by using LVO-NSs as the anode and active carbon as the cathode, delivering an energy density of 61.9 W h·kg −1 at a power density of 12.75 kW·kg −1 . This electrode design strategy of synergistic morphology and crystal structure provides a new route for the development of high-power and long-life energy storage devices.